2015
DOI: 10.1039/c5ee00120j
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis-less inverted CH3NH3PbI3 planar perovskite hybrid solar cells with 18.1% power conversion efficiency

Abstract: The inverted CH3NH3PbI3 planar hybrid solar cells exhibited better device efficiency and stability and lower hysteresis than the normal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
616
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,124 publications
(640 citation statements)
references
References 37 publications
21
616
0
3
Order By: Relevance
“…2d) 31 ; it has been shown that cells with fullerene organic n-type charge collection layers exhibit negligible hysteresis in their J-V curves 32 . We interpret this to indicate that a large surface defect density is generated at the interface between the perovskite and compact TiO2, likely during perovskite crystallisation, whereas the organic materials appear not to induce such a high density of defects 32 .…”
Section: Photovoltaics (Pvs)mentioning
confidence: 99%
“…2d) 31 ; it has been shown that cells with fullerene organic n-type charge collection layers exhibit negligible hysteresis in their J-V curves 32 . We interpret this to indicate that a large surface defect density is generated at the interface between the perovskite and compact TiO2, likely during perovskite crystallisation, whereas the organic materials appear not to induce such a high density of defects 32 .…”
Section: Photovoltaics (Pvs)mentioning
confidence: 99%
“…Noel et al [153] and Dane et al [154] used Lewis bases such as pyridine to treat the perovskite films in order to reduce recombination centers, enhancing the photoluminescence intensity and lifetime. In addition, it has been widely observed that [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) molecules, [155,156] either as an interlayer or mixed as bulk heterojunction structure, are able to passivate defects and alleviate or even eliminate hysteresis. [76] Although the defect passivation process significantly enhances the device performance and decreases the hysteresis, it is found that the time interval for charge trapping and detrapping ranges within milliseconds, [157] or even nanoseconds, [158] which is much shorter than the typical time for the hysteretic behavior.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Spin coating ensures flexibility in adopting either the one step process (i.e., using one ink made of a mixture of the two precursors) or the sequential step deposition (e.g., lead iodide first and then methylammonium iodide) for forming polycrystalline perovskite films. 22 Heo et al, 23 fabricated an inverted planar-structured 23 Although efficiencies achieved with spin coating have been high, ensuring good levels of reproducibility and thickness and morphology control, the sizes of the module have been relatively small and the technique does not really represent an effective solution for the scale up of perovskite solar cell manufacturing. A large percentage of the ink volume is wasted during the spin coating process, leading to a substantial increase in costs and exposure to potentially harmful chemicals.…”
Section: Spin Coatingmentioning
confidence: 99%